A Case of Bilateral Permanent Subluxation of the Lateral Meniscus - Jun Suganuma; Tadashi Sugiki; Yutaka Inoue (Case Reports in Orthopedics)
We report a case of bilateral, permanent subluxation of the lateral meniscus. To our knowledge, the present case is the first reported description of bilateral irreducible anterior dislocation of the posterior segment of the lateral meniscus. This disorder is characterized by a flipped meniscus sign of the lateral meniscus on sagittal magnetic resonance images of the knee joint, with no history of trauma or locking symptoms. A detailed examination of serial magnetic resonance images of the lateral meniscus can help differentiate this condition from malformation of the lateral meniscus, that is, a double-layered meniscus. We recommend two-stage treatment for this disorder. First, the knee joint is kept in straight position for 3 weeks after the lateral meniscus is reduced to the normal position. Second, if subluxation of the lateral meniscus recurs, meniscocapsular suture is then performed. Although subluxation of the lateral meniscus without locking symptoms is rare, it is important to be familiar with this condition to diagnose and treat it correctly.